Pengaruh Kinerja Situs Web Terhadap Kepuasan Dan Loyalitas Pelanggan di E Commerce - Putri Syabila Hidayat; Muhammad Irwan Padli Nasution (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
This research aims to examine the effect of website performance on customer satisfaction and loyalty in e-commerce. E-commerce has become an important platform in e-commerce, and website performance has become a critical factor in achieving customer satisfaction and loyalty. In this research, the conceptual framework used includes three main constructs: website performance, customer satisfaction, and customer loyalty. Website performance is measured along several dimensions, including access speed, reliability, user interface, and content quality. Customer satisfaction is measured as the customer's perception of the quality of service and shopping experience on an e-commerce website. Customer loyalty is measured through repeat purchase intentions and recommendations to others. The research results show that website performance has a significant positive influence on customer satisfaction in e-commerce. Website performance dimensions, such as access speed and reliability, are critical in creating customer satisfaction. Apart from that, customer satisfaction also has a significant positive influence on customer loyalty. Satisfied customers tend to have a higher intent to make repeat purchases and recommend a website to others. The practical implication of this research is the importance of improving website performance to achieve customer satisfaction and loyalty in e-commerce. Business people should pay attention to aspects such as access speed, reliability, user interface, and content quality in the development and maintenance of their websites. Apart from that, efforts to increase customer satisfaction must also be the main focus, because customer satisfaction has a significant impact on customer loyalty.